(3eHOC GdGNJUGU GdLfGFj GdYGdej (B: s (3GdfXQjI hGdJWHjb (B/ s - (3cQjeI YHOGddg eMeO EOQGg s; (3CMeO YhV HdGd (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2015)
(3JfGhdfG aj gPg GdOQGSI eHOC GdGNJUGU GdLfGFj GdYGdej HGYJHGQg BdjI ef GdBdjGJ GdbGfhfjI GdeJGMI hGdbGOQI Ydi VeGf Mb GdVMGjG aj EfUGa bVGFj aYGd, hhVY MO dEadGJ GdeLQejf ef GdYbGH, MjK CVMi gPG GdeHOC ef GdeHGOF GdbGfhfjI GdJj JMce SQjGf GdfU GdLfGFj ef MjK GdecGf aj GdJTQjYGJ GdhWfjI, eY JaQOg Yf HGbj GdeHGOF GdbGfhfjI GdEbdjejI GdTNUjI (B- (3GdYjfjI , Hchfg ehVhY JJhGLO LRFjGJg Hjf bhGYO GdbGfhf GdOhdj GdYGe hGdbhGfjf GdLfGFjI GdhWfjI, HTcd jLYd EecGfjI eYGdLJg HUaI eSJbdI Yf Cj efgeG CeQkG UYHkG(B.s
This study has subject the principle of international penal competence as one of the legal possible mechanism to assure the right of the victims in effective justice and to put an end to escape of punishment. This principle has become one of principles ruling the application of penal text in the espace in the national legislations, but it is distinct from other legal principles: territorial, personal, real, as a subject which elements is dvised between international public law and national penal laws. That is why its study can not be separated from any of them.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2015.s
. (3HHdjhLQGajG(B: (3UaMGJ (B-302: 336.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3eaghe GdGNJUGU s; (3JejR GdGNJUGU Yf GdhdGjI hGdUdGMjI GdbVGFjIs; (3eHOC GdGNJUGU GdEbdjejs; (3GdbjhO GdhGQOI Ydi eHOC GdGNJUGU GdEbdjejs; (3GdeHGOF GdecedI deHOC GdGNJUGU GdEbdjejs; (3GdGNJUGU GdLfGFj aj GdTQjYI GdGSdGejIs; (3eHOC GdGNJUGU GdLfGFj GdYGdejs; (3GdWHjYI GdbGfhfjI deHOC GdGNJUGU GdLfGFj GdYGdejs; (3CSS GdGdJRGe HeHOC GdGNJUGU GdOhdj GdYGdejs; (3GdTQYjI GdELQGFjI deHOC GdGNJUGU GdOhdj GdYGdejs; (3JHfj GdJTQjY GdhWfj ddTQYjI GdehVhYjIs; (3GMJQGe bGYOI GdMce GdMGFR dbhI GdTjAs; (3GdUYhHGJ GdbGfhfjI aj JWHjb eHOC GdGNJUGU GdLfGFj GdYGdejs; (3fWGb JWHjb eHOC GdGNJUGU GdLfGFj GdYGdejs; (3LQjeI GdbQUfIs; (3GdLQGFe GdefXeI GdYGHQI ddMOhOs; (3GdJWHjbGJ GdbVGFjI GdeQahYI habG ddeHOCs; (3eaghe GdGNJUGU s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2015